GENERAL CONCEPTIONS OF PHRASE, WORD COMBINATION AND PHRASEOLOGICAL UNITS - Bektoshev Otabek Kodiraliyevich; Mamurova Shahlo Sultanovna (Galaxy International Interdisciplinary Research Journal, 2022)
The article talks about phrases, word combinations and phraseological units. The vocabulary of the language includes not only words, but also fixed phrases. Fixed phrases with a more complex composition are called phraseologisms or phraseological combinations (phrases). The branch of linguistics that studies phraseologisms is called phraseology. Due to the fact that phraseologisms enter the lexicon of the language, phraseology is considered a branch of linguistics that belongs to the field of lexicology.